Digital Natives as Budding Journalists: College TV Stations' Uses of Twitter. (September 2019) - Cozma, Raluca; Hallaq, Tom
This content analysis examines how award-winning student-run TV stations use Twitter to promote their work and to communicate with followers on campus and beyond. As digital natives and budding professionals, broadcast journalism students should showcase some of the best practices in social-media use. Variables under scrutiny include levels of activity and interactivity on Twitter feeds, popularity of accounts, and focus of tweets. The findings are alarming and suggest that journalism education lags behind shifts in the industry.